The 100 : A Ranking of the Most Influential Persons in History - Hart, Michael H. (London Simon & Schuster, 1993)
Explaining his ratings, the author presents 100 people who swayed the destinies of millions of people, determined the rise and fall of civilizations or transformed the course of history.
Include Illustrations and Index
Keywords: Biography